Experimental and CFD Investigation of a Modified Uneven-Span Greenhouse Solar Dryer in No-Load Conditions under Natural Convection Mode - Abderrahman Mellalou; Walid Riad; Salma Kaotar Hnawi; Abdelaziz Tchenka; Abdelaziz Bacaoui; Abdelkader Outzourhit (International Journal of Photoenergy)
An uneven-span modified greenhouse dryer was constructed and tested in no-load conditions under natural convection mode under the weather conditions of Marrakech, Morocco, for two distinct days. Moreover, a CFD evaluation of the uneven-span greenhouse dryer was performed as tool to visualize the air temperature distribution inside the dryer. For validating the CFD model, the temperature variations along the hours of the day were compared to the experimental results. A good agreement is obtained between the computed and measured inside air temperature with a difference not exceeding 8.46°C, with a correlation coefficient (r) and root mean square percentage deviations (e) 0.94 and 8.17, respectively. Furthermore, the maximum inside air temperature was measured to be 56°C and 52°C while the minimum inside relative humidity was measured to be 17% and 12%, for day-1 and day-2, respectively. The benefice of using asphalt as a floor covering material was revealed as an efficient way to heat the inside air at low solar radiations. The performances of the dryer were evaluated by the percentage of net heat gain variation as a way to validate the effectiveness of the dryer. This latter is found to be equal to 46% and 48% for the two days, respectively.